Research advances in synthesis of nanocarbon-based photocatalysts and their applications for photocatalytic conversion of carbon dioxide to hydrocarbon fuels - Sun, Hongqi; Wang, Shaobin (American Chemical Society, 2014)
Hydrocarbon fuels are the most important sources of energy in modern society because of their natural abundance, stability, and high energy density. However, the emissions of carbon dioxide from them and the associated global warming effect impose worldwide pressure on the use of sustainable solar energy and carbon dioxide transformation and sequestration. Photocatalytic conversion of CO2 to fuels using semiconductors is proposed as an effective solution. Morerecently, nanocarbons, such as carbon nanotube, graphene oxide, and graphene, possessing high thermal conductivity, high theoretical specific surface area, unique carrier mobility, low-dimensional structure, and sp2-hybridized carbon configuration, have shown promotion to photocatalysis. It has been proven that nanocarbon/semiconductor hybrids can be a competitive materialcompared to traditional metal oxides for CO2 reduction. This review summarizes the recent research advances in the synthesis of nanocarbon hybrid photocatalysts and their applications in photocatalytic reduction of CO2 to hydrocarbons. The roles of nanocarbons in extending light absorption, increasing separation of carriers, band gap engineering, and preferred CO2 adsorptionin manipulating activity/selectivity are discussed. The studies in this topic will facilitate the design of advanced functional materials for energy innovation via solar energy use.